Conductive vitrimer nanocomposites enable advanced and recyclable thermo-sensitive materials. Issue 34 (26th August 2020) - Wang, Sheng; Ma, Songqi; Cao, Lijun; Li, Qiong; Ji, Qing; Huang, Juncheng; Lu, Na; Xu, Xiwei; Liu, Yanlin; Zhu, Jin
Abstract : Vitrimers with high thermal expansion rate were innovatively explored to produce advanced and recyclable thermo-sensitive conductive nanocomposites and sensors. Abstract : Smart polymeric materials based on the positive temperature coefficient (PTC) effect have been widely utilized; nevertheless, the negative temperature coefficient (NTC) effect and poor repeatability severely limit their advanced applications. Here, for the first time, vitrimers were exploited to fabricate smart nanocomposites with high PTC intensity, superior repeatability and no NTC effect based on their high thermal expansion rate and cross-linking nature. The PTC behavior can be facilely tuned by adjusting the vitrimer matrix or CB content. Moreover, vitrimer nanocomposites exhibited excellent recyclability and the regenerated ones preserved the PTC behavior pretty well. Finally, they demonstrated great potential to be employed in thermal-sensitive sensors. This work will open a door to developing thermo-sensitive materials (or devices) from vitrimers.